2001
DOI: 10.1021/je000054o
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibria for Binary Mixtures of CO2 with 2-Methyl-2-propanol, 2-Methyl-2-butanol, Octanoic Acid, and Decanoic Acid at Temperatures from 313.15 K to 353.15 K and Pressures from 3 MPa to 24 MPa

Abstract: Phase behaviors of mixtures of CO2 with 2-methyl-2-propanol, 2-methyl-2-butanol, octanoic acid, and decanoic acid were measured with a variable-volume view-cell apparatus from 313.15 K to 353.15 K and from 3 MPa to 24 MPa. The results were correlated by the multifluid−nonrandom lattice fluid (MF−NLF) equation of state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Only vapor-liquid phase equilibrium can be observed under the experimental conditions. 25 measured the bubble pressure (in the liquid phase) of the CO 2 + tertbutanol system at (333.15, 343.15, and 353.15) K. Only the liquid phase equilibrium data were obtained in their work. Kim et al 26 also reported the VLE phase equilibrium data for this system merely at 343.2 K. In this work, the VLE data at (331.9, 341.6, and 351.3) K are listed in Table 3 and shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only vapor-liquid phase equilibrium can be observed under the experimental conditions. 25 measured the bubble pressure (in the liquid phase) of the CO 2 + tertbutanol system at (333.15, 343.15, and 353.15) K. Only the liquid phase equilibrium data were obtained in their work. Kim et al 26 also reported the VLE phase equilibrium data for this system merely at 343.2 K. In this work, the VLE data at (331.9, 341.6, and 351.3) K are listed in Table 3 and shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, high-pressure phase equilibrium data have never been reported in the literature. For the CO 2 + tert-butanol system, Heo et al 25 have measured the VLE data via a nonanalytical method. Kim et al 26 also measured the VLE for the CO 2 + tert-butanol system at temperatures of (323.2 and 343.2) K and pressures from (60 to 120) bar.…”
Section: Introductionmentioning
confidence: 99%
“…Equations of state (EoSs) are useful to correlate the experimental data available and extrapolate the data into conditions for which no experimental data is available. A number of EoSs have been used to describe the experimental data for the systems mentioned above. , The EoSs available have however a number of shortcomings. They have a very limited predictive ability for systems not previously studied.…”
mentioning
confidence: 99%
“…A number of EoSs have been used to describe the experimental data for the systems mentioned above. 22,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The EoSs available have however a number of shortcomings. They have a very limited predictive ability for systems not previously studied.…”
mentioning
confidence: 99%
“…Therefore the decrease in C * D in our experiment must indicates the absorption of the surfactant into the supercritical CO 2 spheres, which in turn decreases the surface concentration of the surfactant. Because solubility of decanonic acid in supercritical CO 2 at 40 • C is 0.178 in mole fraction at 10.3 MPa and is 0.306 at 7.54 MPa (Heo et al 2001), a 0.5 mm diameter supercritical CO 2 sphere can absorb 1.5 × 10 −7 mol decanonic acid at 40 • C and 7.54 MPa. Assuming that the boundary layer of a rising 0.5 mm diameter supercritical CO 2 sphere is twice the diameter of the sphere itself, the sphere can encounter a maximum of 1.5 × 10 −8 mol of decanonic acid.…”
Section: Resultsmentioning
confidence: 99%